Cover Image, Volume 11, Issue 4. (11th July 2017) - de Assis, Camilla Abbati; Houtman, Carl; Phillips, Richard; Bilek, E.M. (Ted); Rojas, Orlando J.; Pal, Lokendra; Peresin, Maria Soledad; Jameel, Hasan; Gonzalez, Ronalds
Abstract : The cover image, by Camilla Abbati de Assis et al., is based on the Modeling and Analysis Conversion Economics of Forest Biomaterials: Risk and Financial Analysis of CNC Manufacturing, DOI:10.1002/bbb.1782 . Abstract : The cover image, by Camilla Abbati de Assis et al., is based on the Modeling and Analysis Conversion Economics of Forest Biomaterials: Risk and Financial Analysis of CNC Manufacturing, DOI:10.1002/bbb.1782 .